2006
DOI: 10.1051/apido:2006051
|View full text |Cite
|
Sign up to set email alerts
|

Botanical sources and sugar concentration of the nectar collected by two stingless bee species in a tropical African rain forest

Abstract: -Nectar foraging by species of two stingless bees was studied in an African tropical rain forest. Both species Hypotrigona gribodoi (2-3 mm) and Meliponula ferruginea (6 mm) collected nectar with a wide range of sugar concentration (H. gribodoi: 14.2-67.4%; M. ferruginea: 9.1-63.4%). H. gribodoi collected nectar of higher sugar concentration than M. ferruginea. Factors that influenced sugar concentration of collected nectar included botanic origin of the nectar, bee species, bee colonies, month of year, time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…The lack of a correlation between nectar volume and sugar concentration can be associated with differences in evaporation and nectar secretion rates, since the concentration of sugars in nectar depends on the rate of pollinator visitation and environmental conditions (solar radiation, rain, wind and temperature) (Kajobe 2007). These results corroborate those reported by Aguilar-Rodríguez et al (2014), who observed a non-significant correlation between volume and sugar concentration for the nectar of the bromeliad Tillandsia macropetala.…”
Section: Nectar Production and Floral Visitorssupporting
confidence: 86%
“…The lack of a correlation between nectar volume and sugar concentration can be associated with differences in evaporation and nectar secretion rates, since the concentration of sugars in nectar depends on the rate of pollinator visitation and environmental conditions (solar radiation, rain, wind and temperature) (Kajobe 2007). These results corroborate those reported by Aguilar-Rodríguez et al (2014), who observed a non-significant correlation between volume and sugar concentration for the nectar of the bromeliad Tillandsia macropetala.…”
Section: Nectar Production and Floral Visitorssupporting
confidence: 86%
“…This implies that the behavior must have been invented independently at Bulindi or else became extinct in these nearby communities (Wrangham 2006). However, while Meliponula bees occur at Sonso and Kibale (Kajobe 2007a;Gruber et al 2009), these bees nest in tree cavities as well as underground (Kajobe 2007b), and ground nests may not be common at these sites. It is not yet known if chimpanzee communities elsewhere in the forestfarm mosaic in Hoima District dig for honey with sticks.…”
Section: Discussionmentioning
confidence: 99%
“…Acacia honey from both species had a significantly (p < 0.05) lower total sugar content than what was found in the other types of honeys. Kajobe (2007) [58] reported that the nectar composition is affected by the floral origin of the nectar, foraging behaviour and environmental factors. In terms of fructose, all tested stingless bee honeys contained higher fructose than glucose except starfruit and acacia from Geniotrigona thoracica.…”
Section: Colour Characteristicsmentioning
confidence: 99%